Design of Android-Based Interactive E-Module Teaching Media for Aviation Radiotelephony Course - Dwi Candra Yuniar; Herlina Febiyanti; Minulya Eska Nugraha; Shabrina Ramadhani (Didaktika: Jurnal Kependidikan, 2024)
This research was made to optimize the learning of Radiotelephony courses by creating new interactive learning media that can be accessed through gadgets and assessing the feasibility of Radiotelephony interactive learning media based on the assessment of media experts, material experts, and student responses. Created using the Research and Development method by Brog and Gall, this study adopts the ADDIE research model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. This research produces learning media that have undergone design and material validation tests. The percentage of validation results by material experts is 85%, and the percentage of validation results by design experts is 88%, so it is included in the very feasible category. Student acceptance of the learning media is shown through the answers to the survey responses, which were distributed where the results reached 89%